1999
DOI: 10.1007/s100510051020
|View full text |Cite
|
Sign up to set email alerts
|

Cation disorder and size effects on the magnetic transition in Ba-containing ferromagnetic manganites

Abstract: PACS. 75.30.Kz Magnetic phase boundaries (including magnetic transitions, metamagnetism, etc.) - 75.50.Dd Nonmetallic ferromagnetic materials - 76.60.-k Nuclear magnetic resonance and relaxation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To verify the generality of the procedure, we measured the temperature dependence of NMR in additional three manganites: La 0.7 Ca 0.15 Ba 0.15 MnO 3 (T C ϭ302 K͒, La 0.7 Ba 0.3 MnO 3 (T C ϭ337 K͒ and La 0.7 Sr 0.15 Ba 0.15 MnO 3 (T C ϭ352.5 K͒. 17 Indeed, we have found that the procedure may be applied equally well to these compounds. The resulting dependence of on T C is displayed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the generality of the procedure, we measured the temperature dependence of NMR in additional three manganites: La 0.7 Ca 0.15 Ba 0.15 MnO 3 (T C ϭ302 K͒, La 0.7 Ba 0.3 MnO 3 (T C ϭ337 K͒ and La 0.7 Sr 0.15 Ba 0.15 MnO 3 (T C ϭ352.5 K͒. 17 Indeed, we have found that the procedure may be applied equally well to these compounds. The resulting dependence of on T C is displayed in Fig.…”
Section: Discussionmentioning
confidence: 99%